What is DevOps? - Davis, Jennifer (Software engineer); Daniels, Ryn (O'Reilly Media, 2018)
As a cross between "development" and "operations," DevOps describes a relatively new way to build and deploy software. But it also defines the collaborative inter-team culture at the heart of the process. This article explains how DevOps can foster trust among individuals and teams throughout your organization